Implementation of Legal Protection for Commercial Sex Workers Experiencing Violence - Diva Josephina; Feronica (Gloria Justitia, 2026)
Prostitution is often referred to as a “victimless crime,” overlooking the various forms of violence that a Commercial Sex Worker (CSW) may experience while performing their work. The social stigma attached to CSWs as “immoral” individuals exacerbates this situation, causing them to frequently receive unfair treatment from law enforcement when they become victims of criminal acts. This study discusses the implementation of legal protection for CSWs in accordance with the laws applicable in Indonesia. Prostitution practices implicitly fulfill elements of employment because they involve the sale of services for income generation. However, this work is considered contrary to the moral norms stipulated in Article 52, paragraph (1), of Law Number 13 of 2003 on Manpower, which results in CSWs not being recognized as workers in an employment relationship. On the other hand, several regions, such as DKI Jakarta, Tangerang City, and Aceh, criminalize prostitution through Regional Regulations, further weakening the legal standing of CSWs.This research employs an empirical juridical method by interviewing two individuals working as CSWs in South Tangerang, supported by secondary data from legislation and relevant literature. Legal protection for CSWs can be found under Law Number 31 of 2014 concerning the Protection of Witnesses and Victims and Law Number 12 of 2022 concerning the Crime of Sexual Violence. However, such protection largely depends on the willingness of CSWs to report themselves as victims, which is often hindered by fear of stigma and re-victimization. This condition places CSWs in a legal vacuum, leaving them without effective protection.